Development and validation of a novel tool to measure tear volume in volumetric unit (microlitre) per minute “the standard international unit (SI) tear strip” - R Balamurugan; Anusuya Bhattacharyya; Phulen Sarma (Indian Journal of Ophthalmology)
The Schirmer strip measures tear volume in millimeters. A major limitation of the Schirmer strip is that it does not measure tear volume in a volumetric unit. Furthermore, the linearity range, lower limit of detection (LLOD), and lower limit of quantification (LLOQ) are not established. In this context, we developed a new filter paper based tear volume strip, which measures tear volume in microlitres (a volumetric unit), with a defined linearity range, LLOD, LLOQ, as well as inter-day and intra-day variability. We used standard Whatman filter paper no. 41, measuring 40 × 5 mm. Balanced salt solution (BSS) was used as a tear surrogate. By placing a specific volume of BSS at one marked end of the paper, we measured the distance travelled by the BSS after one minute. Different volumes of BSS (0.5, 1, 2, 4, 8, and 16 μl) were used, and the distance travelled by the BSS drop was recorded. Linearity was evaluated, and the LLOQ and LLOD were determined. Scale data were generated within the linearity range (10 replicates for each). Percentage recovery was calculated, and inter-day and intra-day variation as well as intra examiner and inter examiner coefficients of variation (CV%) were evaluated. High linearity (r2 = 0.976) was observed across all the tested volumes (0.5–16 μl), However, linearity improved within the tested volume range of 1–8 μl (r2 = 0.996). With an LLOD of 0.538 μl and an LLOQ of 1.63 μl, data for the scale were generated from 2–8 μl. Overall, volumetric recovery ranged from 97.34%–104%. The intra-day CV% ranged from 4.576% (for 2 μl) to 1.911% (for 5 μl) and 1.71% (for 7 μl). The inter-day CV% ranged from 1.715 (7 μl) to 4.36% (for 2 μl). The intra examiner CV% ranged from 0.422% (for 7 μl) to 2.66% (for 2 μl). The inter examiner CV% ranged from 1.93% (7 μl) to 3.69% (for 2 μl). This new tear volume measuring tool (named SI tear strip) represents a valuable tool for the measurement of tear volume (in μl) per unit time. This tool may be very helpful for the quantitative evaluation of dry eye patients and functional assessment of lacrimal glands.